To beat or not to beat a tick: comparison of DNA extraction methods for ticks (Ixodes scapularis) - Ammazzalorso, Alyssa D.; Zolnik, Christine P.; Daniels, Thomas J.; Kolokotronis, Sergios-Orestis (PeerJ, 2015)
Background. Blacklegged ticks (Ixodes scapularis) are important disease vectors in the United States, known to transmit a variety of pathogens to humans, including bacteria, protozoa, and viruses. Their importance as a disease vector necessitates reliable and comparable methods for extracting microbial DNA from ticks. Furthermore, to explore the population genetics or genomics of this tick, appropriate DNA extraction techniques are needed for both the vector and its microbes. Although a few studies have investigated different methods of DNA isolation from ticks, they are limited in the number and types of DNA extraction and lack species-specific quantification of DNA yield. Methods. Here we determined the most efficient and consistent method of DNA extraction from two different developmental stages of I. scapularis—nymph and adult—that are the most important for disease transmission. We used various methods of physical disruption of the hard, chitinous exoskeleton, as well as commercial and non-commercial DNA isolation kits. To gauge the effectiveness of these methods, we quantified the DNA yield and confirmed the DNA quality via PCR of both tick and microbial genetic material. Results. DNA extraction using the Thermo GeneJET Genomic DNA Purification Kit resulted in the highest DNA yields and the most consistent PCR amplification when combined with either cutting or bead beating with select matrices across life stages. DNA isolation methods using ammonium hydroxide as well as the MoBio PowerSoil kit also produced strong and successful PCR amplification, but only for females. Discussion. We contrasted a variety of readily available methods of DNA extraction from single individual blacklegged ticks and presented the results through a quantitative and qualitative assessment.
Keywords: Arthropod; Vector-borne; Blacklegged tick; Tick; DNA extraction; Nucleic acids; DNA quantification